2014
DOI: 10.1037/a0038214
|View full text |Cite
|
Sign up to set email alerts
|

The role of expression and race in weapons identification.

Abstract: Emotional expressions can signal intentions and so possess the power to moderate social inferences. Here we test whether stereotypes implicitly elicited by a stigmatized racial outgroup member are moderated by facial expression. Participants classified pictures of guns and tools that were primed with pictures of Black and White male faces posing angry, happy, and neutral expressions. Across the three measures examined—response latencies, error rates, and automatic processing— facial expression modulated implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Furthermore, happy primes moderated this difference to be statistically insignificant. Alternatively, in study one, there was no difference in response times for Black and White neutral primes; whereas in study two trends followed previous studies which demonstrate that when primed with neutral facial expressions, people more readily and often times inaccurately associate Black Americans with guns than White Americans (Kubota & Ito, 2014). This suggests that when viewing neutral facial expressions context matters much more than happy or angry faces.…”
Section: Emotional Expressionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, happy primes moderated this difference to be statistically insignificant. Alternatively, in study one, there was no difference in response times for Black and White neutral primes; whereas in study two trends followed previous studies which demonstrate that when primed with neutral facial expressions, people more readily and often times inaccurately associate Black Americans with guns than White Americans (Kubota & Ito, 2014). This suggests that when viewing neutral facial expressions context matters much more than happy or angry faces.…”
Section: Emotional Expressionsupporting
confidence: 66%
“…Finally, because primes of only one expression were seen in study two, participants completed fewer total trials-120 instead of 360. Results revealed that in both studies, angry primes significantly increased the degree to which Black primes facilitated responses to guns relative to White C H A P T E R 0 8 DEBIASING primes (Kubota & Ito, 2014). Furthermore, happy primes moderated this difference to be statistically insignificant.…”
Section: Emotional Expressionmentioning
confidence: 73%
“…To provide a more precise (and higherpowered) estimate of the magnitude of racial bias after adult and child primes, we conducted an internal meta-analysis with a random-effects model (Borenstein et al, 2009), using the RT, error rate, and PDP-automatic estimate data from both experiments. For the RTs and error rates, we created indices of racial bias (Kubota & Ito, 2014). For example, the RT metric in Experiment 1 was calculated as follows: (White prime-Black-stereotypic trials minus Black prime-Blackstereotypic trials) + (Black prime-non-stereotypic trials minus White prime-non-stereotypic trials).…”
Section: Discussionmentioning
confidence: 99%
“…Facial cues to emotion provide a quick indication of intent, and racial stereotypes may be implicitly activated by subtle cues related to face processing. Using a gun/tool classification task, Kubota and Ito (2014) primed participants with Black and White male faces posing with angry, happy, or neutral expressions just before making the classification decision. Generally, findings showed that a Black angry prime elicited negative stereotypes, whereas a Black smiling prime diminished negative responses, suggesting that emotional expression can attenuate automatic racial stereotyping, thereby diffusing expectations of threat, similar to what may occur in everyday encounters.…”
mentioning
confidence: 99%